Dermatology for the Allergist - Dennis Kim, MD; Richard Lockey, MD (World Allergy Organization Journal, 2010)
Allergists/immunologists see patients with a variety of skin disorders. Some, such as atopic and allergic contact dermatitis, are caused by abnormal immunologic reactions, whereas others, such as seborrheic dermatitis or rosacea, lack an immunologic basis. This review summarizes a select group of dermatologic problems commonly encountered by an allergist/immunologist. Keywords: dermatology, dermatitis, allergy, allergic, allergist, skin, disease